2020
DOI: 10.1080/19768354.2020.1838607
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of synaptic vesicle exocytosis reduce surface expression of postsynaptic glutamate receptors

Abstract: Bafilomycin A1, a vacuolar H + -ATPase inhibitor, and botulinum toxin B and tetanus toxin, both vesicle fusion inhibitors, are widely known exocytosis blockers that have been used to inhibit the presynaptic release of neurotransmitters. However, protein trafficking mechanisms, such as the insertion of postsynaptic receptors and astrocytic glutamatereleasing channels into the plasma membrane, also require exocytosis. In our previous study, exocytosis inhibitors reduced the surface expression of astrocytic gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It has been shown that Rph3A expression at striatal synapses and its interaction with GluN2A‐containing NMDAR are increased in a rat model of Parkinson's disease 32 . GluN2A‐containing NMDARs translocate to the synapses due to the mobilization of pre‐assembled NMDARs from non‐synaptic pools 33 . However, the selective aggregation of these receptors is because Rph3A selectively binds to GluN2A, but not to other GluN2‐type regulatory NMDAR subunits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that Rph3A expression at striatal synapses and its interaction with GluN2A‐containing NMDAR are increased in a rat model of Parkinson's disease 32 . GluN2A‐containing NMDARs translocate to the synapses due to the mobilization of pre‐assembled NMDARs from non‐synaptic pools 33 . However, the selective aggregation of these receptors is because Rph3A selectively binds to GluN2A, but not to other GluN2‐type regulatory NMDAR subunits.…”
Section: Discussionmentioning
confidence: 99%
“…GluN2A-containing NMDARs translocate to the synapses due to the mobilization of pre-assembled NMDARs from non-synaptic pools 33. However, the selective aggregation of these receptors is because Rph3A selectively binds to GluN2A, but not to other GluN2-type regulatory NMDAR subunits.…”
mentioning
confidence: 99%
“…Neurons were transferred to the stage of a laser-scanning confocal microscope (LSM 700, Carl Zeiss, Germany) and viewed with a 40× objective (numerical aperture, 1.3). Eight optical sections spanning 8 µm in z -dimension were collected (1-µm steps) and combined through z -axis into a compressed z stack (Woo et al 2020 ; Kim et al 2021 ). PSD95 was excited at 488 nm with an argon ion laser.…”
Section: Methodsmentioning
confidence: 99%
“…The signals were detected using an Imagine ABI680 Analyzer (Amersham). Specific bands from western blots were quantified using ImageJ software and normalized against GAPDH as previously described (Woo et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%